Epidemiology of breast cancer in Zaporizhzhia region from 2011 to 2016. - A. І. Shevchenko; O. М. Levyk; A. S. Alieshchenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2018)
Breast cancer is the most important problem of modern oncology.